NERVE TISSUE DAMAGE IN DENTAL IMPLANTATION PRACTICES (British Journal of Global Ecology and Sustainable Development, 2024)
In the process of performing Dental spelling, damage to the trigeminal nerve branches (such as the inferior alveolar, tongue, chin or suborbital) is a complication that can develop.Direct damage to nerve fibers can occur as a result of injury, inflammation, or an infectious factor. Often, trigeminal nerve branches are affected during anesthesia manipulation, Valve separation, bone augmentation Assembly, osteotomy, and the installation of a titanium support directly into the bone. Since the restoration of the affected nerve fibers is very problematic, the best tactic to treat such complications is prevention. Therefore, it is very important for the doctor to understand the features of the histology and anatomy of the nerves of the face-jaw area and to have information about the symptoms that accompany their injuries.Practicing doctors must take into account the tamoils of comparative diagnosis, identify the causes of the development of certain symptoms in order to carry out various practices. Treatments for lesions of the Trigeminal nerve branches include the use of various pharmacological drugs, follow-up with physiotherapy, or even the removal of a problematic dental implant.